Newborn Screening for CAH-Challenges and Opportunities - Natasha L. Heather; Anna Nordenstrom (MDPI AG, 2021)
Newborn screening for congenital adrenal hyperplasia (CAH) using 17-hydroxyprogesterone (17-OHP) as an indicator of disease was first introduced in the 1970s [...]